PENGARUH STRATEGI RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS DAN KEMANDIRIAN BELAJAR - Rahmawati, Dinda; Irawati, Riana; Sudin, Ali (Jurnal Pena Ilmiah, 2019)
This research was based on the idea that the ability of mathematical representation and student learning independence was something that could be developed through good learning. One of the learning that was suitable to improve the ability of mathematical representation and student learning independence by using strategy of REACT. This research was a quasi-experimental research usingÂ  non equivalent control group design. The sample in this research were grade VB as experiment class and grade VA as control class. The instruments in this research include the test result of learning ability of mathematical representation, the scale of learning independence attitude, observation guidelines, student journal and field notes. The results of result with significance level = 0.05 (5%) showed that strategy of REACT can improve the ability of mathematical representation and student learning independenc. Strategy of REACT is also better than conventiona learning approach in improving mathematical representation and learning independence.